Royal Society Scientific Meeting: Extracellular vesicles in the tumour microenvironment. (20th November 2017) - Pink, Ryan Charles; Elmusrati, Areeg A.; Lambert, Daniel; Carter, David Raul Francisco
Abstract : Cancer cells do not grow as an isolated homogeneous mass; tumours are, in fact, complex and heterogeneous collections of cancer and surrounding stromal cells, collectively termed the tumour microenvironment. The interaction between cancer cells and stromal cells in the tumour microenvironment has emerged as a key concept in the regulation of cancer progression. Understanding the intercellular dialogue in the tumour microenvironment is therefore an important goal. One aspect of this dialogue that has not been appreciated until recently is the role of extracellular vesicles (EVs). EVs are small vesicles released by cells under both normal and pathological conditions; they can transfer biological molecules between cells leading to changes in phenotype. EVs have emerged as important regulators of biological processes and can be dysregulated in diseases such as cancer; rapidly growing interest in their biology and therapeutic potential led to the Royal Society hosting a Scientific Meeting to explore the roles of EVs in the tumour microenvironment. This cross-disciplinary meeting explored examples of how aberrant crosstalk between tumour and stromal cells can promote cancer progression, and how such signalling can be targeted for diagnostic, prognostic and therapeutic benefit. In this review, and the special edition of Philosophical Transactions of the Royal Society B that follows, we will provide an overview of the content and outcomes of this exciting meeting. This article is part of the discussion meeting issue 'Extracellular vesicles and the tumour microenvironment'.